PENGARUH IKLAN DI TELEVISI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SECARA ONLINE - Agustiana, Umi Bela; Setiadi, Yulius Wahyu (Yayasan Insani Mandiri Santani, 2024)
This study aims to determine the effect of advertising on television on online product purchase decisions in Cempaka Permai Village, Bengkulu City. This research is a quantitative research with a sample of 336 respondents, using accidental sampling technique, that is, all residents of the population are directly targeted and research objects. Data collection techniques using observation and questionnaires. Data analysis techniques using classical assumption test, simple linear regression, and hypothesis testing. The results of this study can be seen from the simple linear regression test. This means that the variable Advertising on Television has a positive influence on online product purchasing decisions. The results of the correlation coefficient also show a result of 0.605, which means that the television advertising variable influences purchasing decisions by 60.5% while the remaining 39.5% is influenced by other variables outside the model.Keywords: Advertising on Television, Online Purchase Decision